Análisis de la responsabilidad social corporativa de las empresas florícolas del sector Lasso, Cantón Latacunga, Provincia De Cotopaxi en el período comprendido enero - diciembre 2011 - Jiménez Mallitásig, Nancy Guadalupe (2013)
The present analyses has as goal show the problems and deficiencies that the flower enterprises have, the purpose is optimize the handling recourses into it, however avoiding the environment pollution on the other hand health problems due to with people who have a direct relative with the chemical products usage. In the first chapter was realized the main research about the theoretical fundamention knowledge that support the present investigative work, though it was getting in point from the Administrative and Financial management, the flower enterprise , and finally the Social Corporative Responsibility. In the second chapter was applied sorts of techniques such as observational, interview and survey techniques, these ones allow as getting a relevant information over the duty which have the flower´s enterprise with the community and the environment. In the third chapter the investigators described the diagnostic, in a macro – micro environment, the FODA, the indicators, the benefits appliances - Social Corporative Responsibility in the flower enterprise, with the aim of emitting conclusions and recommendations which allow for helping to solve the problems that makes troubles to get from the objective.